Manganese Accumulation and Toxicity, and Superoxide Dismutase Activity in Vegetable Soybean (Glycine Max (L.) Merr.) - Djafruddin, Rosmaidar (2001)
Manganese toxicity is one of the growth limiting factors under acidic conditions. Some plants accumulate Mn more in the top than in the root, while others accumulate more in the root than in the top. Vegetable soybean is an indicator plant that can be used to determine the mechanism of toxicity. Part of the plant tissue that accumulates the highest Mn needs to be extracted so as to determine the activity of superoxide dismutase (SOD). In view of this, a series of experiments was conducted to determine the accumulation of Mn in the tissues (leaf, stem, root and pod) of vegetable soybean, toxic level of Mn in solution culture, time-dependent of Mn accumulation in the tissue and the effect of Mn concentration on superoxide dismutase activity under different time of plant growth. Five experiments were conducted in glass house and laboratories at UPM. Experiment 1 was a sand culture experiment to determine the distribution of Mn accumulation in the plant tissues. Experiment 2 and 3 were solution culture experiments to observe toxic level of Mn. Experiment 4 was used to determine time-dependent of Mn accumulation, while experiment 5 was used to study the effect of Mn and time on superoxide dismutase activity. The results showed that the highest accumulation of Mn in vegetable soybean was in the leaves. The Mn concentration corresponding to 20% reduction in dry weight was 20 uM. Plant accumulated Mn more during vegetative stage compared to generative stage. Increasing the time of growth decreased the accumulation of Mn in the 5 and 25 uM of Mn treatments Degeneration of plant cell in toxic condition (25 uM) affected the growth of plant and inhibited nutrient movement from the root to the shoot. Enzyme extraction showed that the activity of superoxide dismutase increased up to 25.36 umol m L-1 of crude enzyme minute-1 at level 15 uM after 20 days of plant age in solution culture.